Use of skin-lightening products among outpatient attendees in a North Indian Hospital - Celestine Wong; Samuel Wong; Howard Tang; Rashi Minocha; Rajesh Singh; Nathan Grills (Wolters Kluwer Medknow Publications, 2017)
In India, fair skin is a highly valued physical attribute. Skin lightener products comprise 60% of the dermatological market. This cross-sectional study was conducted in the general medical outpatient clinics of Champa Christian Hospital to elucidate the perceptions of fair skin and determinants/pattern of skin lighter use. Demographics, pattern of skin lightener use and incidence of side effects, perceptions of lighter skin tones were the main outcomes and measures studied. The use of skin lighteners was highly prevalent in our study population. Believing that lighter skin is beneficial for self-esteem is a predictor for skin lightener use. Higher education was associated with lower perceived benefits of fairer skin and therefore reduced skin lightener use. Further education and increased community awareness are important to address the issues surrounding potential over-use of skin-lightening products.